Measurement system to study the relationship between forearm EMG signals and wrist position at varied hand grip force - Sidek, S. Naim; Mohideen, Ahmad Jazlan H. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/